2015
DOI: 10.1002/jca.21422
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the depletion‐red cell exchange program with the Spectra Optia and the isovolemic hemodilution‐red cell exchange method with the COBE Spectra in sickle cell disease patients

Abstract: Technical performance and packed RBC unit consumption were not compromised when switching from the COBE Spectra IHD/RBCx protocol to the depletion/RBCx protocol on the Spectra Optia. Tolerability was equal for both protocols. J. Clin. Apheresis 31:429-433, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…Several studies have described the performances of the SO device when using the RBCX technique associated (SO/DE) or not (SO) with the depletion step for patients with SCA . These studies showed similar performance of SO compared to CSP both associated and not associated with DE.…”
mentioning
confidence: 99%
“…Several studies have described the performances of the SO device when using the RBCX technique associated (SO/DE) or not (SO) with the depletion step for patients with SCA . These studies showed similar performance of SO compared to CSP both associated and not associated with DE.…”
mentioning
confidence: 99%
“…RCE can be modified to include an initial phase of isovolemic hemodilution (or “depletion”—removing RBCs to a specified Hct while instilling saline [or 5% albumin], which is then followed by RCE) . This procedure can reduce the volume of RBCs needed for the exchange and thus reduce donor exposure—that is, for the same volume of RBCs used, the efficiency of HbS removal is improved because fewer RBCs need to be removed . However, this is not an option for all patients, as the preprocedure Hct must be taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…However, this is not an option for all patients, as the preprocedure Hct must be taken into account. One study selected only patients with preprocedure Hct levels of more than 26% and stable hemodynamic status . A second study required a preprocedure Hct level of 23% or more and decreased the patient's Hct up to 6% during the isovolemic hemodilution phase (if baseline Hct level was 23%‐31%) or 8% (if baseline Hct level was ≥32%) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Complications of acute hemoreduction may be seen in both the automated and manual setting and include hypovolemia (dizziness, syncope, headache, weakness) and a possible risk of acute neurologic complications caused by acute anemia. Symptoms of hypovolemia maybe reduced by administration of a normal saline bolus before the hemoreduction.…”
mentioning
confidence: 99%